Rancang Bangun Sistem Monitoring Karyawan Berbasis Web di PT Global Marketing Technology - Fikry Ananda; Albar Raya; Jupron Jupron (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
This study details the development of an employee monitoring platform that combines electronic leave administration features with integrated logistics distribution tracking at PT Global Marketing Technology. The crucial obstacle found in the field is that the biometric attendance system has not been linked to secondary licensing procedures. Employees still use paper forms to request approval, making the human resources division highly vulnerable to calculation errors due to leave quota clashes with national holidays. In addition, the corporation does not yet have an instrument to monitor the location of delivery couriers in real-time. The linear sequential approach (Waterfall) is applied as a software engineering method, which includes the phases of Requirement identification, architectural Design, coding, testing, and Maintenance. The trials show that this web application is capable of automatically calculating effective working days, shortening the approval bureaucracy chain, while providing a GPS tracking function for field logistics couriers. It can be concluded that this platform has successfully overcome conventional administrative hurdles and boosted the visibility of personnel supervision by management.